The prominence of choral music in the search for, and preservation of, an African identity: A study focusing on the role of choral composers in the formation of black nationalism during and after the colonial era in South Africa - Nelani, Athenkosi (Rhodes University, Faculty of Humanities, Department of Music and Musicology)
In South Africa, choral music has been prominent in schools, churches, and community choirs since the 19th century. However, the majority of South Africans know little of the history of indigenous choral music. This study investigates the origins of South African indigenous choral music, its canonic figures, and their contribution to this genre in promoting an African identity among the indigenous people of South Africa. Using the methodological lens of historical ethnomusicology, this thesis explores the genesis of choral music in South Africa. Choral music was introduced to the region when it was first colonised by the Dutch East India Company in 1652. Missionaries established institutions in the villages of the local people and translated the Bible and hymn books into the local languages. These actions had lasting consequences for music, and choral singing was greatly advanced. In addition, in this work early composers of South African indigenous choral music are recognised in an effort to establish a choral canon. Three definitive choral periods are recognised, namely those of the first-generation, second-generation, and post-colonial composers. Using this historical framework, this thesis investigates the social and political influence these composers had on African identity during the liberation struggles in the late colonial era and during the early apartheid period. The history and compositions of the composers are discussed, including how they used their compositions as political tools and as mouthpieces to communicate societal issues of concern to the indigenous people during and after the colonial era.
Keywords: Choral music -- South Africa; Choral singing -- South Africa; Black people Race identity -- South Africa; Black nationalism -- South Africa; Composers, Black -- South Africa; Amakwaya